The Flexibility of Portuguese Study Plans as a Consequence of the Bologna Process on Economics Undergraduate Majors: a Comparison with Europe - Monteiro, H.; Ferreira-Lopes, A. (Dinâmia Working Paper 2005/47, 2005)
In this paper we perform a comparative analysis of the study plans in Economics undergraduate majors between Portugal and the best European institutions for the school year 2004-05. We find Portuguese undergraduate majors to be less flexible regarding the European reference reality, with a greater proportion of required courses and a smaller set of optional courses. Our study provides information about the essential courses to be included in the study plans of Economics undergraduate majors in Portugal with length reduced to three years, and about their required or optional nature. The study's conclusions are compared with the recommendations from the Bologna Process implementation report for Economics and Management, ordered by the Portuguese Ministry of Higher Education. Taking into account the Bologna declaration stated objectives of greater compatibility and comparability of higher education systems, we deem necessary to revise some of the conclusion from this report regarding the flexibility of the new study plans.